Delivering the vision public services for the information society and the knowledge economy - Milner, Eileen M. 1963- (Routledge, 2002)
Political rhetoric surrounding the role of information and knowledge in society in the twenty-first century is often thrown into sharp relief by the realities of practice. Delivering the Vision explores the way in which public service visions have developed globally and how successful they have been in contributing to major social and economic change.